An overview of some natural antioxidants used in meat and poultry products - Karre, Elizabeth A. (Kansas State University, 2009)
In response to recent claims that synthetic antioxidants have the potential to cause toxicological effects and consumers’ increased interest in purchasing natural products, the meat and poultry industry has been seeking sources of natural antioxidants to replace synthetic antioxidants, which are currently being used by the industry. Due to their high phenolic compound content, fruits and other plant materials provide a good alternative to conventional antioxidants. Plum, grape seed extract, cranberry, pomegranate, bearberry, pine bark extract, rosemary, oregano, other spices, irradiated almond skins, and green tea have functionality as antioxidants in meat and poultry products. Pomegranate, pine bark extract, cinnamon, and cloves have exhibited stronger antioxidant properties than some of the synthetic antioxidants currently used by the meat and poultry industry. Of the discussed natural antioxidants, grape seed extract, cranberry, sage extract, thyme extract, basil extract, ginger extract, pine bark extract, and a Chinese 5-spice blend had the highest percent antioxidant activity (% AOA). (The quality of the antioxidant used may also impact its ability to function as an antioxidant). Some of these natural antioxidants have influenced color and sensory properties of finished meat and poultry products. Plum products used in meat and poultry products have increased redness of the finished product. In some products such as pork sausage or uncured meats, an increase in red color may be desired. Grape seed extract, pine bark extract, rosemary, almond skin powder, some spices and green tea extract have been shown to impact the color of finished meat or poultry products. Plum products and many other spices affect the overall sensory properties of meat or poultry products as well. Depending on the finished product, consumers may view these changes as positive or as negative. When selecting a natural antioxidant to use in a meat or poultry product, the sensory and quality impact on the product should be considered in order to achieve a product with the desired traits.
Keywords: Antioxidants in meat; Antioxidants in poultry; Spice antioxidants; Fruit antioxidants; Plant antioxidants; Agriculture, Food Science and Technology (0359)